PENGARUH SELF REWARD DENGAN KEPUASAN DIRI DAN MOTIVASI KERJA PADA FEMALE GEN Z - Ilmiyah, Dwi Erni Mazroatul; Qurratu’aini, Nafia Ilhama; Sholikhah, Afifatus (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the influence of self reward on self-satisfaction and work motivation in working Generation Z (Female Gen Z) women. This generation is known to have high attention to work-life balance and mental health, so self reward is one of the factors that can increase self-satisfaction and work motivation. This study uses a quantitative approach with an explanatory research method. The results showed that self reward has a positive and significant effect on self-satisfaction and work motivation. In addition, self-satisfaction also has a positive effect on work motivation. These findings confirm that self reward strategies can improve the psychological well-being and work productivity of Female Gen Z. The implications of this study highlight the importance of implementing a balanced self reward in the work environment to increase employee satisfaction and motivation.